(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Albee’s play which deals with the troubled and hollow family ties, is A Delicate Balance. This play concerns with the family of four – a passive husband, an imperious wife, an alcoholic sister-in-law and a much divorced daughter – their problems are exacerbated when they are visited by their friends (a couple named Harry and Edna), who have experienced a nameless terror. The balance of security, happiness and comfort is so delicate, in this family, that it gets upset when the friends move in the family with their terror because terror, for them, is infectious like plague. The play is set in the living room of a suburban house, and the action is centered on six characters. C.W.E. Bigsby comments, “These characters are linked either by familial ties or by the familiarity of long association, which they falsely confuse with “love”. Against this setting they act out a ritual which, like those in Eliot’s play and Albee’s own earlier work, forces them to face the specters of their own fears”.